Examining the conceptual and empirical distinctiveness of Agreeableness and "dark" personality items. Issue 3 (1st December 2020) - Vize, Colin E.; Miller, Joshua D.; Lynam, Donald R.
Abstract: Objective: A growing research literature has focused on what have been termed "dark" personality traits/constructs. More recently, the "dark factor" of personality has been proposed as a unifying framework for this research. To date, little work has rigorously investigated whether the traits/constructs investigated in the context of the dark factor can be captured by existing models of normative personality, namely Agreeableness from the Five‐factor Model. Thus, the "dark factor" may be an instance of the "jangle" fallacy, where two constructs with different names are in fact the same construct. Method: We used a preregistered approach that made use of bass‐ackward factor analysis, structural equation modeling, and nomological network analysis to investigate the distinction between the D factor and Agreeableness. Results: Agreeableness and the D factor were similar in their coverage of antagonistic personality content, strongly negatively related (latent r  = −.90), and showed near perfect profile dissimilarity ( rICC  = −.99). Conclusions: The results suggested that the D factor can be understood as the opposite pole of Agreeableness (i.e., antagonism) and not as a distinct construct. We discuss the implications for researchers interested in continuing to advance the study of antagonistic personality traits.